Improving Justice and Security in Indonesia: The Role of Australia-Indonesia Partnership for Justice (AIPJ2) (Global Focus, 2021)
Located in a strategic area and consisting of various ethnicities and religions, Indonesia is vulnerable to transnational crimes and violent extremism. Furthermore, this also creates social injustice, where groups are marginalized. Therefore, Indonesia continues to strive to improve justice and security for its citizens, one of which is by increasing cooperation with other countries or international organizations. This article aims to explain how Indonesia-Australia cooperation’s role in maintaining justice and security in Indonesia through the second period of the Australia- Indonesia Partnership for Justice (AIPJ2). The author will use qualitative methods and use secondary data, where data will be collected from previous studies and related literature. The results of this research show that AIPJ2, through its support and programs to several Civil Society Organisations and government institutions, has contributed to positive changes in the justice and security sectors in Indonesia, even though these changes were done gradually and has to face challenges.